2017
DOI: 10.1021/acs.iecr.6b04562
|View full text |Cite
|
Sign up to set email alerts
|

Production of Benzene Carboxylic Acids and Small-Molecule Fatty Acids from Lignite by Two-Stage Alkali-Oxygen Oxidation

Abstract: Carboxylic acids are widely used in industry as a kind of important chemical materials, and it is very promising to produce carboxylic acids from lignite. The traditional alkalioxygen oxidation of lignite does not consider the complex structure of lignite, and the structures with different reactivities are treated under identical and harsh reaction conditions, resulting in a low yield of carboxylic acids. We propose a twostage oxidation process of lignite to increase the yield and mitigate the harsh reaction c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This indicates that during the thermal decomposition process of the AH NPs@cellulose composite aerogels, the AH NPs were degraded into metallic oxides, which results in the absorption of the decomposition products originating from the cellulose aerogel matrix. The adsorbed compounds were transferred to carbon by catalytic action in the solid phase …”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicates that during the thermal decomposition process of the AH NPs@cellulose composite aerogels, the AH NPs were degraded into metallic oxides, which results in the absorption of the decomposition products originating from the cellulose aerogel matrix. The adsorbed compounds were transferred to carbon by catalytic action in the solid phase …”
Section: Results and Discussionmentioning
confidence: 99%
“…At the same time, the process of decomposition releases plenty of water and will not produce toxic, flammable, or corrosive gas, which has contributed to the reduction of the concentration of oxygen on the surface. After that, the porous metallic oxides, generated during the combustion process, not only retard the heat spread but also suppress the release of fuel from the solid phase to the combustion area . Then, the nanometal particles can form a continuous and dense network-structured protective layer without forming a crack that damages the flame-retardant effect, which can serve as a thermal insulation layer of the original polymer below the layer while isolating oxygen to prevent combustion. On the basis of these facts, the flame-retardant properties of cellulose composites aerogel are greatly improved.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These may be derived from lignin or tannin, which include a wide variety of polycondensed aromatics (Hernes and Hedges, 2000;Waggoner et al, 2015). Other non-pyrogenic OM sources of condensed aromatic OM are abundant in the geosphere, including woody peat, coal, kerogen, and oil (Yoshioka and Ishiwatari, 2005;Hammes et al, 2007;Wang et al, 2012;Hartman et al, 2015;Li et al, 2017). Still other studies have found that nonpyrogenic OM can be readily transformed to condensed aromatic OM, which would appear to be pyrogenic, through photolytic, microbial, or chemical degradative processes (Glaser and Knorr, 2008;Chen et al, 2014;Waggoner et al, 2015;DiDonato et al, 2016).…”
Section: Methodology/conceptual Issuesmentioning
confidence: 99%